2016
DOI: 10.1186/s12993-016-0111-2
|View full text |Cite
|
Sign up to set email alerts
|

Age, environment, object recognition and morphological diversity of GFAP-immunolabeled astrocytes

Abstract: BackgroundFew studies have explored the glial response to a standard environment and how the response may be associated with age-related cognitive decline in learning and memory. Here we investigated aging and environmental influences on hippocampal-dependent tasks and on the morphology of an unbiased selected population of astrocytes from the molecular layer of dentate gyrus, which is the main target of perforant pathway.ResultsSix and twenty-month-old female, albino Swiss mice were housed, from weaning, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 105 publications
2
41
0
Order By: Relevance
“…Environmental factors can also induce epigenetic changes. In a recent study that assessed how environment impacted young vs. old astrocytes, it was reported that aged mice from a standard environment could not distinguish between stationary and displaced objects (Diniz et al, 2016 ). Upon further examination of the astrocytes in these animals, the authors found two distinct morphological phenotypes and speculated that aging and environment reduce the complexity of astrocytes (Diniz et al, 2016 ).…”
Section: Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental factors can also induce epigenetic changes. In a recent study that assessed how environment impacted young vs. old astrocytes, it was reported that aged mice from a standard environment could not distinguish between stationary and displaced objects (Diniz et al, 2016 ). Upon further examination of the astrocytes in these animals, the authors found two distinct morphological phenotypes and speculated that aging and environment reduce the complexity of astrocytes (Diniz et al, 2016 ).…”
Section: Astrocytesmentioning
confidence: 99%
“…In a recent study that assessed how environment impacted young vs. old astrocytes, it was reported that aged mice from a standard environment could not distinguish between stationary and displaced objects (Diniz et al, 2016 ). Upon further examination of the astrocytes in these animals, the authors found two distinct morphological phenotypes and speculated that aging and environment reduce the complexity of astrocytes (Diniz et al, 2016 ). This agrees with previous literature showing morphological changes between young and old astrocytes (Kanaan et al, 2010 ; Cerbai et al, 2012 ; Jyothi et al, 2015 ).…”
Section: Astrocytesmentioning
confidence: 99%
“…Furthermore, this integrated representation of object information relies on a well-characterised integrated neural network involving the perirhinal cortex (processing object identity familiarity and novelty), the hippocampus (processing the spatial location of objects) and the medial frontal cortex, which contributes to memory for the temporal order of objects (see Warburton & Brown, 2015). Consistent with age-related changes in this neural network, recognition memory involving object-place information and temporal order is sensitive to ageing (Diniz et al, 2016;Hernandez et al, 2015) and perturbation of this memory network is associated with increased risk of dementia (Hirni et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…EE was demonstrated to be a useful tool to improve cognitive function and reduce anxiety-like behaviour in many models of neurodegenerative diseases (Sampedro-Piquero and Begega, 2017). Many authors described that EE animals performed better in the NOR test compared to those animals that were housed in SC (Diniz et al, 2016;Sampedro-Piquero and Begega, 2017). .…”
Section: Discussionmentioning
confidence: 99%